Cytotoxic Activities of Ethanol Extract, Nonpolar Semipolar, and Polar Fractions of Dioscorea esculenta L.) on MCF7 Cancer Cell - Haryoto, H (Universitas Muhammadiyah Surakarta, 2019)
One of the disease that have a high contribution to the death of women in the world is breast cancer. It leads to the research and exploration to find its cure. This study is conducted to know the anti-cancer activity onethanol extract, nonpolar, semipolar, and polar fractions of lesser yam (Dioscorea esculenta L.) herbs. It also aims to find out the content of compound on semipolar fraction Dioscorea esculenta L. herbs. The extraction was carried out using maceration technique with 96% ethanol as solvent. Then, the fractination was done using vacuum liquid chromatography method with n-hexane and acetone as mobile phase with the ratio of 9:1, 8:2, 7:3, 6:4, and 5:5. After that, the phytochemical test was undertaken using the thin layer chromatographywith n-hexane and acetone as mobile phase with proportion 7:3. Meanwhile, the cytotoxic test was conducted using MTT assay method with IC50calculation was counted using linear regression between the log concentration and the percentage of living cells. The semipolar fraction of Dioscorea esculenta L. herbs has IC50value of 632,42 Âµg/mL, whereas the ethanol extract, nonpolar and polar fractions have the IC50 value 1000 Âµg/mL. Furthermore, the compound of the semipolar fraction of Dioscorea esculenta L. herbs are saponins, terpenoids, alkaloids, and phenolics.